The impact of toll road exit infrastructure development on land use and land values in adjacent areas (Case: eastern toll road exit in Probolinggo Regency) - Okky Fransila Arganata; Deva Fosterharoldas Swasto (Journal of Sustainability Science and Technology, 2022)
The development of trans-Java road infrastructure is intended to increase regional accessibility and mobility. Probolinggo Regency is one of the regencies traversed by the Trans Java Road, one of its six toll road exits being the eastern toll road exit. By comparing conditions before and after the existence of the eastern toll road exit, this study sought to investigate changes in land usage and land values in the vicinity of the exit. This study employed a qualitative method, collecting data through in-depth interviews and observation. The results indicate that the identification of land use changes after the construction of the toll road exit is not significant because the changes occurred at a greater distance from the location of the exit. By designating the region as toll road infrastructure, settlements, and areas of activity, the paddy fields and dry fields surrounding the exit have been transformed into built-up land. However, since the construction of the eastern toll road exit, land value fluctuations have climbed by between 104% and 140%. In other words, the presence of constructed infrastructure does not necessarily have a direct effect on land-use changes. Nonetheless, it can have a substantial impact on land prices in settlements near the toll road exit.